An attenuated vaccinia vaccine encoding the severe acute respiratory syndrome coronavirus-2 spike protein elicits broad and durable immune responses, and protects cynomolgus macaques and human angiotensin-converting enzyme 2 transgenic mice from severe acute respiratory syndrome coronavirus-2 and its variants - Ishigaki, Hirohito; Yasui, Fumihiko; Nakayama, Misako; Endo, Akinori; Yamamoto, Naoki; Yamaji, Kenzaburo; Nguyen, Cong Thanh; Kitagawa, Yoshinori; Sanada, Takahiro; Honda, Tomoko; Munakata, Tsubasa; Higa, Masahiko; et al. (Frontiers in Microbiology, 2022)
As long as the coronavirus disease 2019 (COVID-19) pandemic continues, new variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with altered antigenicity will emerge. The development of vaccines that elicit robust, broad, and durable protection against SARS-CoV-2 variants is urgently required. We have developed a vaccine consisting of the attenuated vaccinia virus Dairen-I (DIs) strain platform carrying the SARS-CoV-2 S gene (rDIs-S). rDIs-S induced neutralizing antibody and T-lymphocyte responses in cynomolgus macaques and human angiotensin converting enzyme 2 (hACE2) transgenic mice, and the mouse model showed broad protection against SARS-CoV-2 isolates ranging from the early-pandemic strain (WK-521) to the recent Omicron BA.1 variant (TY38-873). Using a tandem mass tag (TMT) -based quantitative proteomic analysis of lung homogenates from hACE2 transgenic mice, we found that, among mice subjected to challenge infection with WK-521, vaccination with rDIs-S prevented protein expression related to the severe pathogenic effects of SARS-CoV-2 infection (tissue destruction, inflammation, coagulation, fibrosis, and angiogenesis) and restored protein expression related to immune responses (antigen presentation and cellular response to stress). Furthermore, long-term studies in mice showed that vaccination with rDIs-S maintains S protein-specific antibody titers for at least 6 months after a 1st vaccination. Thus, rDIs-S appears to provide broad and durable protective immunity against SARS-CoV-2, including current variants such as Omicron BA.1 and possibly future variants.